The Role of external debt on the economic growth of the Gambia - KASSAMA, Alieu (KDI School, 2016)
Previous studies that have attempted to establish a relationship between external debt and economic growth yielded different conclusions. Nonetheless, there was no previous study in the case of The Gambia. However, this study examines the “the Role of External Debt on the Economic Growth of The Gambia” by using time series data for the period 1970 to 2012. We employed the Error Correction Mechanism (ECM) to regress economic growth on external debt and debt service plus other explanatory variables. The regression results showed that economic growth is influenced negatively by both current flows of external debt and past accumulation of external debt. The negative impact of past accumulation of external debt conforms to the debt overhang literature. However, external debt service has a positive impact on economic growth both in the short run and long run in the case of The Gambia. As a result, the government of The Gambia should endeavor to refocus its existing policies and institutional arrangements in contracting foreign loans. In addition, aggressive measures are required to curtail government expenditures in order to revise the increase in domestic interest rates. Furthermore, the government should built and strengthen the capacity of the Debt Management Office (DMO).
Thesis(Master) --KDI School:Master of Development Policy,2016